2022
DOI: 10.1111/1753-6405.13175
|View full text |Cite
|
Sign up to set email alerts
|

Out of the trenches; prevalence of Australian veterans among the homeless population and the implications for public health

Abstract: Objectives: To examine the prevalence of Australian Defence Force veterans among people sleeping rough and explore their health and social needs relative to non-veteran rough sleepers.Method: Analysis of responses to the Vulnerability Index -Service Prioritisation Decision Assistance Tool (VI-SPDAT) collected from 8,027 rough sleepers across five Australian States from 2010-2017.Results: Veterans were found to comprise 5.6% of people sleeping rough in Australia, with veterans reporting having spent an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Less than half of the people on the By‐Name List were connected to specialist homelessness services when they completed the VI‐SPDAT. Additionally, there may be gender differences in help‐seeking from homelessness services (Wood et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Less than half of the people on the By‐Name List were connected to specialist homelessness services when they completed the VI‐SPDAT. Additionally, there may be gender differences in help‐seeking from homelessness services (Wood et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Veterans across the United States are at risk for the development of an array of serious illnesses, 20,21 increased risk of homelessness, 22 risk for moral injury, 23,24 physical disabilities, 25 and posttraumatic stress disorder 26,27 ; this includes female veterans. Thus, the development of a consistent model for palliative care delivery would be beneficial to all veterans, especially those beyond the reach of urban VHA facilities.…”
Section: Journal Ofmentioning
confidence: 99%
“…14 Another study found that 5.6% of people sleeping rough in Australia were veterans, with veterans more likely to spend longer periods of time sleeping rough. 15 Also, 1300 persons who identified as current or former Corresponding author: Duncan Wallace, School of Psychiatry, University of New South Wales, Sydney, NSW 2052, Australia. Email: d_wallace@ozemail.com.au serving members of the ADF were assisted by Specialist Homeless Services in 2020-21 with 54% identifying as homeless and 46% at risk of homelessness.…”
mentioning
confidence: 99%
“… 14 Another study found that 5.6% of people sleeping rough in Australia were veterans, with veterans more likely to spend longer periods of time sleeping rough. 15 Also, 1300 persons who identified as current or former serving members of the ADF were assisted by Specialist Homeless Services in 2020–21 with 54% identifying as homeless and 46% at risk of homelessness. 3 However, Nielssen et al 16 did not find a single DVA client among 2140 adults who attended an inner-city homeless hostel clinic and had been admitted to a hospital in NSW between 2008 and 2021, suggesting either a lack of individuals identifying as former serving ADF members or a lack of uptake of DVA services by veterans who are homeless or at-risk of homelessness.…”
mentioning
confidence: 99%